Dielectric properties of Sm, Nd and Fe doped Bi1.5Zn0.92Nb1.5O6.92 pyrochlores - (:unkn) unknown (ELSEVIER SCI LTD, 2011)
New pyrochlore ceramics have been produced by doping Sm and Nd into the Bi site and Fe into the Nb site in the Bi1.5Zn0.92Nb1.5O6.92 (BZN) pyrochlore. Doped pyrochlore ceramics were produced by conventional solid state mixing of oxides at different doping levels using the compositions of Bi1.5-xSmxZn0.92Nb1.5O6.92, B1.5-xNdxZn0.92Nb1.5O6.92 and Bi1.5Zn0.92Nb1.5-xFexO6.92-x. The solubility limit of cations was determined as x = 0.13, 0.18 and 0.15 for Sm, Nd and Fe, respectively. While Sm and Nd increased the dielectric constant (E), Fe doping led a decrease in E. Dielectric constant of Sm and Nd doped BZN increased to 199 at x = 0.13 (Sm) and to 219 at x = 0.18 (Nd). At low Fe dopings (x = 0.05), the dielectric constant of BZN increased to 242 but decreased to 211 at x = 0.15. The dielectric losses were lower for Sm and Nd dopings than Fe but in all cases it was lower than 0.006. The dielectric constant of Sm, Nd and Fe doped BZN ceramics was nearly independent of frequency within the frequency range between 1 kHz and 2 MHz, but decreased considerably with temperature between 20 and 200 degrees C. Temperature coefficient of Sm doped BZN (-354 ppm/degrees C) was lower than Nd and Fe doped BZN ceramics at solubility limits (-538 ppm/degrees C for Nd and -565 ppm/degrees C for Fe). (C) 2010 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Dielectric properties; Bismuth zinc niobate pyrochlore; Dopants; LOW-FIRING CERAMICS; CRYSTAL-CHEMISTRY; DIFFRACTION